2005
DOI: 10.1021/jp053138i
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Magnetic Properties of Manganese-Incorporated Zinc Sulfide Nanorods Synthesized by a Solvothermal Process

Abstract: Manganese-incorporated ZnS (MnxZn1-xS) nanorods were synthesized by a simple solvothermal process. Synthesized nanorods were single crystalline. Manganese incorporation in the ZnS lattice induces a phase transformation from hexagonal wurtzite to cubic zinc blende structure. The diameter of the nanorods increased with the increase of Mn concentration. Intense orange luminescence at approximately 585 nm was observed for the nanorods. Six-line hyperfine splitting was observed in the EPR spectra for lower Mn conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 25 publications
9
159
1
Order By: Relevance
“…This result confirms that the fluorescence emission is not simply due to contributions from Mn 2+ in Zn 1-x Mn x S shell; Mn 2+ with T d site symmetry has an emission peak typically centered at 580 ~ 590 nm due to its 4 T 1 → 6 A 1 transition. 24 The lack of Mn 2+ emission is consistent with the EPR results suggesting that Mn 2+ is not in a highly ordered ZnS shell structure. However, even with the thicker ZnS shell, no emission from tetrahedral Mn 2+ can be discerned.…”
Section: Resultssupporting
confidence: 84%
“…This result confirms that the fluorescence emission is not simply due to contributions from Mn 2+ in Zn 1-x Mn x S shell; Mn 2+ with T d site symmetry has an emission peak typically centered at 580 ~ 590 nm due to its 4 T 1 → 6 A 1 transition. 24 The lack of Mn 2+ emission is consistent with the EPR results suggesting that Mn 2+ is not in a highly ordered ZnS shell structure. However, even with the thicker ZnS shell, no emission from tetrahedral Mn 2+ can be discerned.…”
Section: Resultssupporting
confidence: 84%
“…26,27 The green band is observed in the samples annealed in Zn vapor, vacuum, or reducing atmosphere, resulting in Zn excess. 28 Green emission was also reported in both undoped and Mn doped ZnS nonorods by Biswas et al, 29 and they concluded that this emission is due to zinc-vacancy related defect states. Our samples were grown in Zn-rich conditions; thus, we believe that the strong emission may be ascribed to the interstitial Zn defect and nonstoichiometric defects.…”
Section: Resultsmentioning
confidence: 63%
“…Narrow band gap IV-VI (IV = Sn, Ge, Pb; VI = S, Te, Se) semiconductors exhibiting infrared (IR) and near-infrared (NIR) optical activity have been extensively studied. Among them, tin chalcogenide based materials such as tin sulfide semiconducting nanomaterial has attained immense importance owing to its interesting potential applications such as photodetectors, optoelectronics, and data storage [3,4]. SnS is a narrow bandgap semiconductor with an optical band gap of direct transitions 1.32-1.5 eV and indirect transitions 1-1.3 eV [5].…”
Section: Introductionmentioning
confidence: 99%